Phospholipase C isoforms in mammalian spermatozoa: potential components of the sperm factor that causes Ca2+ release in eggs. - Parrington, J; Jones, M; Tunwell, R; Devader, C; Katan, M; Swann, K (2002)
Injection of a soluble protein factor from mammalian spermatozoa triggers Ca2+ oscillations in mammalian eggs similar to those seen at fertilization. This sperm factor also generates inositol 1,4,5-trisphosphate and causes Ca2+ release in sea urchin egg homogenates and frog eggs. Recent studies have indicated that the sperm factor may be an inositol-specific phospholipase C (PLC) activity. This study investigated whether any of the commonly known PLC isoforms are components of the sperm factor. PLCbeta, PLCgamma and PLCdelta isoforms were shown to be present in boar sperm extracts. However, upon column fractionation of sperm extracts, none of the PLC isoforms detected correlated with the ability to cause Ca2+ release in eggs. In addition to our previous work on recombinant PLCs, it was also shown that PLCdelta3, PLCdelta4 and its splice variant PLCdelta4 Alt1 fail to cause Ca2+ release. The recently discovered 255 kDa PLCepsilon isoform also appears unlikely to be a component of the sperm factor, as fractionation of sperm extracts on a gel filtration column demonstrated that the peak of Ca2+-releasing activity was associated with fractions of 30-70 kDa. These findings indicate that the sperm factor that triggers Ca2+ release in eggs does not appear to have a known PLC isoform as one of its components.